Legal Consequences of Unilateral Cancellation of Sale and Purchase Agreements on E-Commerce Platforms - Marisha Marisha; Rona Roveria; Justia Afnuri; Ulan Dari (Verdict: Journal of Law Science, 2026)
The rapid expansion of e-commerce in Indonesia has transformed sale and purchase agreements into multilayered electronic transactions involving consumers, sellers, platforms, payment systems, and logistics providers. This article formulates three focused questions: how electronic sale and purchase agreements are formed under Indonesian law; what legal consequences arise from unilateral cancellation by sellers, buyers, or platforms; and what cancellation governance model can protect consumers while preserving fair responsibility among transaction actors. Using normative juridical research with statutory, conceptual, case-based, and limited comparative approaches, this study analyses legislation, doctrine, Indonesian journal literature, and selected court-based studies on online sale disputes. The article finds that unilateral cancellation is not per se unlawful, but it becomes legally defective when it violates pacta sunt servanda, good faith, consumer rights, evidentiary duties, or statutory limits on standard clauses. Its consequences may include continued performance, rescission with restitution, compensation, invalidity of unfair clauses, administrative sanctions, and platform liability where the platform exercises active control over transaction architecture or dispute resolution. The article proposes a proportional cancellation governance model requiring transparent reasons, prior notice where feasible, evidence preservation, time-bound refund, and differentiated liability among sellers, buyers, and platforms.